The power of fun : how to feel alive again - Price, Catherine, 1978- (The Dial Press, 2021)
"In our always-on, productivity-addicted lifestyles, we tend to think of the pursuit of fun as being indulgent, even immature and childish. When we do find the time to relax or care for ourselves, we tend to turn to activities that are not actually restorative: binging Netflix, scrolling through Twitter, or indulging our FOMO on Instagram. Through years of research, journalist Catherine Price has learned the truth: far from being frivolous or a distraction, fun is actually the secret to achieving our goals. If you reorient your life around what you personally find fun-true fun-you will be happier and healthier. You will be more productive, less resentful, and less stressed. You will have more energy, for yourself and for other people. You will find community and a sense of purpose. You will feel alive again"--